Steroid pulse therapy for VKH during pregnancy: a safe and effective option? - Umashri Sundararaju; Shanmathi Subramanian; Hamrish Kumar Rajakumar (Orphanet Journal of Rare Diseases)
Abstract Vogt–Koyanagi–Harada syndrome (VKH) is a rare autoimmune condition affecting melanocyte-containing tissues such as the eyes, skin, hair, inner ear, and meninges. The disease progresses through four phases: prodromal, uveitic, convalescent, and recurrent. Symptoms include headaches, photophobia, ocular inflammation, and auditory disturbances. Although the etiology behind VKH is unknown, it is believed to be triggered by viral infections such as the Epstein‒Barr virus or Cytomegalovirus in genetically predisposed individuals. It is diagnosed by confirming bilateral ocular involvement and ruling out other conditions, such as tuberculosis. It is managed by corticosteroids, with steroid pulse therapy being effective for controlling inflammation and improving outcomes. However, it carries significant risks, such as hypertension, infections, and electrolyte imbalances. Managing VKH during pregnancy can be challenging and requires a multidisciplinary approach, as corticosteroid use can affect both maternal and fetal health. Steroid therapy is crucial for controlling disease, but it can lead to complications such as infections, fetal growth restriction, and potential neurodevelopmental issues in infants. Future research should focus on optimizing steroid regimens, understanding the long-term effects of corticosteroid use during pregnancy, and developing personalized treatment strategies to improve maternal and fetal outcomes in VKH management.